Evaluating the Equivalence of Health Care Ratings by Whites and Hispanics - Morales, Leo S. (2000)
PURPOSE: This study was designed to assess the equivalence of a/health care ratings scale administered to non-Hispanic white and Hispanic survey respondents. METHODS: We sent 18,840 questionnaires to a random sample of patients receiving medical care from a physician group association concentrated in the western United States; 7,093 were returned (59% adjusted response rate). Approximately 90% of survey respondents self-identified as white/Caucasian (n = 5,508) or Hispanic/Latino (n = 713). Interpersonal and technical aspects of medical care were assessed with 9 items, all administered with a 7-point response format: the best, excellent, very good, good, fair, poor, and very poor, with a “not applicable” option. Item response theory procedures were used to test for differential item functioning between white and Hispanic respondents. RESULTS: Hispanics were found to be significantly more dissatisfied with care than whites (effect size=0.27; P <0.05). Of the 9 test items, 2 had statistically significant differential item functioning (P <0.05): reassurance and support offered by your doctors and staff and quality of examinations received. However, summative scale scores and test characteristic curves for whites and Hispanics were similar whether or not these items were included in the scale. CONCLUSIONS: Despite some differences in item functioning, valid satisfaction-with-care comparisons between whites and Hispanics are possible. Thus, disparities in satisfaction ratings between whites and Hispanics should not be ascribed to measurement bias but should be viewed as arising from actual differences in experiences with care.